(untitled) (RuMoRes, 2009)
The purpose of this paper is to discuss the concept of semiotic boundary, according to Yuri Lotman, in culture texts in the daily press, generating new information and semiosis in our present time, thanks to the procedures of signs systems which constitute them. The communication takes place in the process of contamination between different sign systems, which allows the understanding of different procedures generated in multiple formats and genres in the different modeling systems. The reflections are complemented by a reading of a newspaper photo.